Evaluación de la calidad De vida relacionada con la salud en Adultos Mayores Institucionalizados Aplicando Las Viñetas Coop-Wonca En Hogares Geriátricos de la ciudad De Bogotá D.C Año 2017 (2017)
The health-related quality of life evaluation of institutionalized older adults was carried out in 3 Geriatric Homes of the city of Bogota in 2017, with a calculates sample of 77 patients calculated, of which 38 patients met the criteria of inclusion. The COOP-WONCA vignettes, in their 7-dimensional format, was used as an evaluation tool, which includes variables of: "Physical Form, Feelings, Social Activities, Daily Activities, Changes in Health Status, Health Status, Pain”. Resulting in a quality of life related to health is Regular in the population surveyed